The prediction of chemical composition and in vitro digestibility of samples of Atriplex halimus by NIR spectroscopy - Andueza D.; Muñoz F.; Murray I. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
As part of a research study of the seasonal variation in composition of the Atriplex halimus in the Aragon region of Spain, 318 plant samples were obtained and analysed for the chemical and in vitro composition: dry matter (DM), ash, crude protein (CP), neutral and acid detergent fibre (NDF, ADF), acid detergent lignin (ADL), in vitro dry matter digestibility (IVDMD), potassium (K), chloride (Cl) and calcium (Ca). Accuracy of determination by NIRS was evaluated by the coefficient of determination in calibration and cross validation (R2 and r2), standard error of calibration (SEC), standard error of cross validation (SECV). The results obtained showed that NIRS could explain 81, 92, 92, 89, 85, 92, 63, 70 and 90 percent, of the variation in ash, CP, NDF, ADF, ADL, IVDMD, Na, K and Cl respectively. NIR spectra of these samples gave useful calibration models for all of these attributes except calcium.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)